Serum and hepatic oxidative damage induced by a diet contaminated with fungal mycotoxin in freshwater silver catfish Rhamdia quelen: Involvement on disease pathogenesis - Souza C.F. (2018)
© 2018 Elsevier Ltd It has been recognized that oxidative stress is implicated in the initiation and progression of diseases due to the excessive formation of free radicals and impairment of the antioxidant defense system, contributing to the mortality of affected animals. The occurrence of a disequilibrium between the antioxidant/oxidant status in serum and liver of freshwater fish fed with aflatoxin B 1 (AFB 1 ) remains poorly understood and limited to only a few oxidant variables. Thus, the aim of this study was to evaluate whether an AFB 1 -contaminated diet causes disturbance on the antioxidant and oxidant status in silver catfish (Rhamdia quelen) of freshwater. Serum and hepatic reactive oxygen species (ROS), metabolites of nitric oxide (NOx), and lipid hydroperoxide increased on days 14 and 21 post-feeding in animals that received AFB 1 contaminated diet compared to the control group (basal diet), while protein carbonylation levels increased on day 21 post-feeding. On the other hand, serum and hepatic antioxidant capacity against peroxyl radical and vitamin C levels, as well as glutathione peroxidase and catalase activities were lower on days 14 and 21 post-feeding in animals that received AFB 1 contaminated diet compared to the control group. No difference was observed between groups regarding the superoxide dismutase activity and glutathione levels. Based on these evidences, an AFB 1 -contaminated diet causes a disturbance on serum and hepatic antioxidant/oxidant system due to lipid and protein damage elicited by excessive ROS and NOx production. Also, the antioxidant defense system was unable to avoid or minimize ROS and NOx deleterious effects, and consequently, the oxidative damage. In summary, this disturbance can contribute to understand the pathophysiology and mortality of fish after the consumption of AFB 1 -contaminated diets.